FRI0512 Involvement of Plexind1/Semaphorin 3E Pathway in the Dysregulation of Vascular Tone Control in Systemic Sclerosis Patients. (10th June 2014) - Mazzotta, C.; Romano, E.; Bruni, C.; Manetti, M.; Lepri, G.; Bellando-Randone, S.; Blagojevic, J.; Chora, I.; Radicati, A.; Matucci-Cerinic, M.; Guiducci, S.
Abstract : Background: The main hallmark of systemic sclerosis (SSc) is vasculopathy characterised by dysregulation of angiogenesis and vascular tone leading to loss of capillaries. The vascular and nervous system have several anatomic similarities that extend to level of the molecular mechanisms. Emerging evidence suggests that proteins involved in transmitting axonal guidance cues, including class III semaphorin families, also play a critical role in blood vessel guidance during physiological and pathological vessel development. Sema3E acts through its receptor plexin-D1 to control endothelial cell positioning and patterning of the developing vasculature. Sema3E is a natural antiangiogenic molecule that causes filopodial retraction in endothelial cells inhibiting cell adhesion by disrupting integrin-mediated adhesive structures. Objectives: The aim of the present study was to investigate if plexin-D1/Sema3E axis could be involved in dysregulated vascular tone control (RF) characteristic of SSc. Methods: Sema3E levels were measured by quantitative colorimetric sandwich ELISA in serum samples from 45 subjects with primary Raynaud's phenomenon (PRF) without ANA, Scl70, ACA positivity, 48 SSc patients and 48 age- and sex-matched healthy controls. Patients were classified according to nailfold videocapillaroscopy (NVC) patterns (early, active and late). Sema3E levels were expressed as median and range and compared by Mann-Whitney U test. Differences were considered significant for p values less than 0.05. Western blot was used to evaluate plexin-D1/Sema3E axis in human dermal microvascular endothelial cells from healthy subjects (H-MVECs) at basal condition and after stimulation with recombinant human VEGF165 (10 ng/ml), lcSSc sera (n=3) and healthy sera (n=3) for 24h. Results: Sema3E sera levels were significantly higher both in PRF subjects (median 0.54 ng/ml) and SSc patients (median 0.67 ng/ml) respect to healthy controls (median 0.19 ng/ml) (both p<0.001). In particular, sema3E levels were significantly higher in SSc patients with early NVC pattern both respect to active/late pattern and PRF (both p<0.05). Moreover, sema3E levels were significantly increased in SSc patients without ulcers compared with patients with digital ulcers (p=0.018). H-MVECs stimulated with SSc sera and SSc-MVECs showed higher levels of the activated plexin-D1 form and sema3E protein expression in respect to basal H-MVECs and healthy sera. No differences were found in plexin-D1/Sema3E axis after challenging with VEGF. Conclusions: Circulating sema3E is significantly increased both in PRF and SSc. Higher sema3E levels are increased in the early stages of SSc without digital ulcers. Our findings suggest that plexin-D1/Sema3E axis might have a role in the dysregulation of vascular tone control. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3227